Factors Determinant Behavior Masters Student in Adopt OJS Website - Titik Kusmantini; Heru Tri Sutiono; R. Hendri Gusaptono; Yekti Utami (CV. Strata Persada Academia, 2023)
Study this aim for confirmation factors determinant master student in adoption of the Online Journal System (OJS) website. To compose a skeleton conceptual about behavior adoption technology information , researcher use two theory base i.e. acceptance model technology (TAM) and theory acceptance and use technology integrated (UTAUT). Sample in study this is Master of Management students at University X amounted to 105 students. Structural model testing techniques using LISREL for verify structural model and validation hypothesis research. Research results identify that there is correlation between 8 factors determinant behavior student in OJS website adoption, factor the is (1) facilitating conditions; (2) perceived usefulnes; (3) perceived easy to use; (4) social approval; (5) result demonstrability; (6) innovation awareness and (8) voluntariness of use. Ability factor determinant the by simultaneously capable shape behavior adoption by 73%. Test results hypothesis reported that four factor like condition facilitating condition, perceived usefulness, perceived easy to use and social approval have significant influence to adoption of OJS websites, and social approval have most significant influence to adoption of OJS website. Implication practical on results study this is important for OJS manager for designing convenient OJS features and templates user to submit articles, as well as important for to do maintenance application.